Species composition, stand structure, and regeneration status of tree species in dry Afromontane forests of Awi Zone, northwestern Ethiopia - Getaneh Gebeyehu (Taylor & Francis Group, 2019)
Species composition, structure, and regeneration status of trees were assessed in five dry Afromontane forests. In each of the forests, trees having ≥5 cm diameter at breast height were identified and measured in 80 quadrats (20 × 20 m2). We compared tree species composition and similarities, stem densities, frequencies, basal area and importance value index of trees. Harvesting index was calculated to 13.3% in the least disturbed and 22.5% in highly disturbed forests. A total of 1,655 individuals representing 38 species and 28 families were recorded. The tree densities varied from 364.1 to 664.1stem ha−1 with an average basal area of 20.7 m2 ha−1. The analysis showed significant differences in basal areas of tree species between the least and highly disturbed forests. Seedling densities ranged from 2000 to 8162.5 stem ha−1 and sapling densities ranged from 512.5 to 2562.5 stem ha−1. The anthropogenic disturbances revealed high degradation of population structure and regeneration statutes of the trees in the studied forest ecosystem. In conclusion, the study provided empirical results on the dominance, population structure, importance value and regeneration status of tree species, which would be instrumental for the development of successful rehabilitation strategies for the studied forests.